2022
DOI: 10.3389/fphar.2022.792794
|View full text |Cite
|
Sign up to set email alerts
|

Moringa Oleifera Lam. in Cardiometabolic Disorders: A Systematic Review of Recent Studies and Possible Mechanism of Actions

Abstract: Cardiometabolic disorders (CMD) have become a global emergency and increasing burden on health and economic problems. Due to the increasing need for new drugs for cardiometabolic diseases, many alternative medicines from plants have been considered and studied. Moringa oleifera Lam. (MO), one of the native plants from several Asian countries, has been used empirically by people for various kinds of illnesses. In the present systematic review, we aimed to investigate the recent studies of MO in CMD and its poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 125 publications
(220 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, while such information already affirms the hypoglycaemic potential of this medicinal plant, data regarding the prominent biochemical mechanisms implicated in the antidiabetic effects of Moringa oleifera have not been critically reviewed. Recently, Louisa and others supported the potential benefits of Moringa oleifera in cardiovascular or metabolic disorders, mainly by ameliorating the undesired pro-inflammatory response and inhibiting oxidative stress by mediating molecular mechanisms such as hindering nuclear factor kappa B (NF-κB) translocation or enhancing the antioxidant response of nuclear factor-erythroid factor 2-related factor 2 (Nrf2) in different preclinical models ( Louisa et al, 2022 ). Thus, there is a need to better understand such intracellular responses of Moringa oleifera within a setting of diabetes or in related metabolic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while such information already affirms the hypoglycaemic potential of this medicinal plant, data regarding the prominent biochemical mechanisms implicated in the antidiabetic effects of Moringa oleifera have not been critically reviewed. Recently, Louisa and others supported the potential benefits of Moringa oleifera in cardiovascular or metabolic disorders, mainly by ameliorating the undesired pro-inflammatory response and inhibiting oxidative stress by mediating molecular mechanisms such as hindering nuclear factor kappa B (NF-κB) translocation or enhancing the antioxidant response of nuclear factor-erythroid factor 2-related factor 2 (Nrf2) in different preclinical models ( Louisa et al, 2022 ). Thus, there is a need to better understand such intracellular responses of Moringa oleifera within a setting of diabetes or in related metabolic complications.…”
Section: Introductionmentioning
confidence: 99%
“…At molecular levels, MO tended to reduce the oxidative stress via activation of a basic leucine zipper transcription factor that links to the promoter domain of the antioxidant response element (Nrf2-ARE) signaling, elevating the expression of Nrf2 target genes and declining the expression of transforming growth factor beta-1 (TGF-β1) signaling [300]. It has been also approved to stimulate the total antioxidant capacity through the suppression of nuclear factor kappalight-chain-enhancer of activated B cells (NF-kB) translocation, upregulation of the Kelch-like ECH-associated protein 1-(Keap1-) nuclear factor-erythroid 2-related factor 2 (Nrf2) (Nrf2/Keap1) system, reducing the activation of protein kinase C, zeta (PKCζ), and inhibiting the NADPH oxidase 4 (Nox4) protein expression [301].…”
Section: Moringa Oleifera and Antioxidantsmentioning
confidence: 99%
“…Dysbiosis in the gut microbiota attributed to various factors leads to substantial physiological shifts and increases the probability of MetS (Wang et al, 2019a(Wang et al, , 2019b. Over the past years, several studies have reported the gut and intestinal microbiome-modulating effects of M. oleifera in MetS indices depicted in Figure 3 (Gao et al, 2017;Louisa et al, 2022;Tian et al, 2021).…”
Section: Gut Microbiota Altering Effectsmentioning
confidence: 99%